A Concise Interference Model for Wireless Sensor Networks using Directional Antennas - Staniec, K.; Miedzinski, B. (Elektronika ir Elektrotechnika, 2012)
The paper focuses on the issue of intra-network electromagnetic interference in wireless sensor networks where multiple sensor nodes are located on an open-space area at random locations. It is assumed that the topology is planar and reliable (i.e. at least two alternative paths exist for each node). Moreover, nodes are equipped with directional antennas for interference reduction. As is demonstrated, in such complex systems a statistical node will experience a regular dependency between the beamwidths of antennas mounted on sensor modules and the overall intra-network radio interference level. Based on the achieved simulated results, a simple formula has been proposed for expressing SNIR of a statistical (average) network node as a function of beamwidth and the number of nodes with a high correlation coefficient. As it turns out, there only of the model parameters is responsive to the scaling of size of the network area – it can be easily calculated then for any other size of the area than one presented in the paper. Ill. 7, bibl. 17, tabl. 1 (in English; abstracts in English and Lithuanian).DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1822